ELECTROPHORETIC DETERMINATION OF AMYLASE IN THE POST-EMBRYONIC STAGE OF LABEO ROHITA (HAM.) - Das, B C (Indian Journal of Fisheries, 2011)
Work on enzyme synthesis, carried out in bacteria, shows that it is not onlygenetically determined but also influenced by culture conditions (Levinthal, 1959).The culture conditions presumably alter the rate at which the exogenous inducerenters the cell, the actual rate of synthesis being a function of the concentrationof the inducer inside the cell (Hogness, 1959). The present research is the first toevaluate the amount of amylase present in post-embryonic Indian freshwater carpand to determine the influence of exogenous yeast Saccharomyces cerevisiae onamylase synthesis in the post-embryonic carp.